Cadmium Induces the Activation, Concentration, and Expression of MTF-1 Protein As a Biomolecular Response of Sea Urchins Deadema setosum - Dominggus Rumahlatu (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
Heavy metal cadmium has toxic effects in the bodies of living organisms.However, the bodies of living organisms have the ability to regulate a wide range of toxic entering the body by using biomolecular response that aims at maintaining cell homeostasis. In this research an induction of cadmium in sea urchins Deadema setosum was carried out. Cadmium was induced in 6 levels of concentration in six treatment groups of D. setosum. Each group consisted of 7 individuals.The examination of MTF-1 protein activation was carried out by immunohistochemical method, the measurement of MTF-1 protein concentration was carried out by the indirect ELISA method (Enzyme Linked Imunoasssay) and the examination of MTF-1 protein expression was carried out by western blotting method. The data were analyzed using descriptive analysis and One Way ANOVA followed by Duncan test 0.05 to determine the mean difference of MTF-1 protein concentration of D. setosum. The research results showed that cadmium induction activated MTF-1 characterized by the condition of liver cells of D. setosum which was brown.The higher the exposure of cadmium concentration on D. setosum, the higher the concentration of MTF-1 expressed